Complications, Reoperations, and Mid-Term Outcomes Following Anterior Vertebral Body Tethering Versus Posterior Spinal Fusion: A Meta-Analysis. Issue 2 (April 2021) - Shin, Max; Arguelles, Gabriel R.; Cahill, Patrick J.; Flynn, John M.; Baldwin, Keith D.; Anari, Jason B.
Abstract : Background: Anterior vertebral body tethering (AVBT) is a growth-modulation technique theorized to correct adolescent idiopathic scoliosis (AIS) without the postoperative stiffness imposed by posterior spinal fusion. However, data are limited to small series examining short-term outcomes. To assess AVBT's potential as a viable alternative to posterior spinal fusion (PSF), a comprehensive comparison is warranted. The purpose of this meta-analysis was to compare postoperative outcomes between patients with AIS undergoing PSF and AVBT. Our primary objective was to compare complication and reoperation rates at available follow-up times. Secondary objectives included comparing mid-term Scoliosis Research Society (SRS)-22 scores, and coronal and sagittal-plane Cobb angle corrections. Methods: We performed a systematic review of outcome studies following AVBT and/or PSF procedures. The inclusion criteria included the following: AVBT and/or PSF procedures; Lenke 1 or 2 curves; an age of 10 to 18 years for >90% of the patient population; <10% non-AIS scoliosis etiology; and follow-up of ≥1 year. A single-arm, random-effects meta-analysis was performed. Deformity corrections, complication and reoperation rates, and postoperative SRS-22 scores were recorded. Results: Ten AVBT studies (211 patients) and 14 PSF studies (1, 069 patients) were included. The mean follow-up durations were similar for both groups. Pooled complication rates were 26% for AVBT versus 2% for PSF, and reoperation rates were 14.1% for AVBT versus 0.6% for PSF with nonoverlapping confidence intervals (CIs). The pooled reoperation rate among studies with follow-up times of ≥36 months was 24.7% in AVBT versus 1.8% in PSF. Deformity correction, clinical outcomes, and mid-term SRS-22 scores were similar. Conclusions: Our study showed greater rates of complications and reoperations with AVBT compared with PSF. Reoperation rates were significantly greater in AVBT studies with longer follow-up (≥36 months). Deformity correction, clinical outcomes, and mid-term SRS-22 scores were similar. While a potential fusionless treatment for AIS merits excitement, clinicians should consider AVBT with caution. Future long-term randomized prospective studies are needed. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.